Bidirectional Associations Between Covid-19 Infection And Mental Disorders - M. Turki; S. Blanji; A. Daoud; S. Ellouze; M. Abdellatif; N. Gargouri; N. Halouani; J. Aloulou (European Psychiatry, 2022)
Introduction The COVID-19 pandemic brought unbearable psychological pressure to people worldwide, because of serious threats to one’s physical health and life. From early stages of this pandemic, concerns have been raised about its effect on mental health. However, we still know little whether pre-existing psychiatric disorder (PD) affects the susceptibility and evolution of this infection.